Impact of technical aspects of vein of Marshall ethanol infusion on mitral isthmus block for persistent atrial fibrillation ablation - Kong, Lingcong; Shuang, Tian; Li, Zheng; Zou, Zhiguo; Pu, Jun; Wang, Xin-Hua (Frontiers in Cardiovascular Medicine, 2022)
Aims Ethanol infusion into the VOM (EIVOM) adjunctive to radiofrequency catheter ablation (RFCA) was a novel approach facilitating mitral isthmus (MIth) block for persistent atrial fibrillation (PeAF); However, there were remarkable disparities in its technical aspects. This study aimed to evaluate the impact of EIVOM technical aspects on acute MIth block. Methods Eighty consecutive patients (63 males, average age 66.4±8.6 years) undergoing de novo PeAF ablation were assigned to different groups. The procedural parameters in “EIVOM first” (n=13) or “RFCA first” (n=13) as well as small dose ([SD], ≤ 4 ml, n=26) or big dose ([BD], >4 ml, n=54) approaches were analyzed to identify the predictors for acute MIth block. Results Compared with the “EIVOM first” approach, the “RFCA first” approach was associated with longer procedural and MIth ablation time (134±27 min vs. 112±17 min; 14.9±5.5 min vs. 9.3±5.1 min, both P<0.05, respectively), but with comparable success of MIth block. The ethanol dose was 6.3±1.5 ml in BD group vs. 3.1±1.0 ml in SD group (P<0.001) and was correlated significantly with the size of Δlow voltage area (r= 0.66, P<0.001). The success of MIth block was 92.6% in BD group vs. 73.1% in SD group, P=0.03. The ethanol dose > 5.75 ml independently predicted successful MIth block (OR 0.428, 95% CI 0.219-0.839, P=0.01). Conclusions Despite the comparable effectiveness on MIth block, the “EIVOM first” approach was associated with shorter procedural and MIth ablation time than the “RFCA first” approach. The ethanol dose in EIVOM was an independent predictor for MIth block.